A Biochar-Based Water Treatment System for Barangay Sawmill,Villaverde, Nueva Vizcaya - Rodolfo, Jonathan S.; Nebrida, Alan P. (Future Science / FSH-PH Publications, 2024)
A comprehensive evaluation was carried out aiming to address water quality issues in Villaverde, Nueva Vizcaya. The research focused on designing and appraising a Biochar-Based Water Treatment System. This review was performed hoping to meet the urgent need for supplying potable water free of contaminants, especially during periods of elevated murkiness caused by heavy precipitation. The foundation of the system relies on utilizing biochar, specifically crafted from coconut husks. This particular biochar is renowned for its remarkable absorptive properties. A treatment system with a flow rate of 250 mL per minute was built using a systematic design process. The efficacy of this system underwent thorough testing, including examining both physical traits and bacteriological integrity. Findings revealed a statistically significant enhancement in water transparency and reduction of microbiological dangers, notably when flow rates were lower. Economic assessments, like breakeven analysis and Benefit-to-Cost ratio, further substantiated the system's feasibility. Over 48 months, it is anticipated the system would recoup initial setup expenses and ongoing operational costs, thus offering a viable and cost-effective choice for the community. Results indicate the Biochar-Based Water Treatment System has ability to supply safe drinking water and provides substantial economic benefits. This system embodies a crucial advancement towards achieving sustainable water management in the Villaverde municipality.